DAMPAK PEMBERLAKUKAN PEMBATASAN KEGIATAN MASYARAKAT (PPKM) LEVEL 4 TERHADAP PEDAGANG KAKI LIMA DI SUKOHARJO - Anisa Dwi Anggraini; Denofata Swastikasari; Lulu Fitriana Laela; Windi Shilvia Puspitasari; Aris Prio Agus Santoso; Bangun Prajadi Cipto Utomo; Sarah Fadila Sarah; An’nissa Ita Yulianti (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2022)
Abstract During the Covid 19 pandemic in Indonesia, it has weakened various sectors of life in society, including the economic sector. Various policy efforts have been carried out by the government to deal with the covid 19 virus outbreak, one of which is the government implementing PPKM level 4. People in the lower middle class such as street vendors really feel the impact that occurred because of this policy most of the street vendors experienced a drastic decrease in turnover due to the PPKM period with strict rules so that community activities were very limited and made traders hampered in the trading process. The formulation of the problem used in this study is to determine the impact caused during the Enforcement of Community Activity Restrictions (PPKM) level 4 in Sukoharjo. One of the objectives of this study was to determine the impact of level 4 Community Activity Restrictions (PPKM) on street vendors, especially in the Sukoharjo area. The method used in this study uses a case study approach with data collection sourced from primary data. The data obtained were Â analyzed qualitatively. Sources of data in this study are the results of questionnaires to the public and the results of interviews from Mr. Suraji as a basic necessities trader, Mrs. Wiji as a kebab seller, and Mr. Afthon as a Labmilk trader in Gentan. The results showed that PPKM level 4 had an impact including: (1) a very significant decrease in turnover; (2) consumers are starting to switch to online shopping instead of offline shopping: (3) unequal government assistance to merchants I.